STABILITY AND BEHAVIOR ANALYSIS OF ANCHORED SHEET PILE WALL IN CASE OF IMPROVING SIANTAR JAKARTA LONG STORAGE CAPACITY - KHARIS PRASIDHI ( NIM : 15006083 ), AWLIA
The author analyzes the stability of the collapse that occurred in the long storage times Siantar. Reinforcement that will be used is anchored sheet pile wall. On that reinforcement, in addition to stability analysis, carried out an analysis of behavior occurs. The purpose of this paper is to know the soil data from interpretation and back-calculation, and obtained reinforcement that qualified the safety factor at these sites as well as to know behaviors that occur on the reinforcement. Coverage of the authors of this report is modeling the data and analyze it. From the process that carried out, the authors interpret the observed data (SPT) to become soil data, and the model is made in accordance with actual circumstances on the field. After that, back calculation of the collapse was done to gain soil data that represent the real situation during the collapse. Then design and analyze the stability of soil reinforcement and behavior. The reinforcement that analyzed is anchored sheet pile wall at a depth of 7, 7.5, and 8 meters. From each depth, anchors were analyzed by using 1 and 2 anchors. For the calculation and analysis, finite element method was used with the help of software Plaxis 8.2. The results are deformation and moment of anchored sheet pile wall with the specification used, and the safety factor obtained from each depth. From these results, we can analyze the safety factor achieved by comparing with the requirement and behaviors that occur on the reinforcement. The conclusion are first, the land consists mainly of silt clay with a depth of up to 7 meters that is very soft and then stiff for the soil in the next depth. Reinforcement that was modeled and analyzed can not maintain stability on the location. Required safety factor is 1.5, and no stability analysis results that meet this requirement. Then, the behavior of reinforcement derived from the results of calculations, different on each sheet pile depths. In addition, installation of anchors with an angle of 45  generate equal vertical and horizontal force, and the vertical deformation that occurs is quite large